2018
DOI: 10.1111/pace.13577
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in symptoms and functional status in patients with atrial fibrillation undergoing catheter ablation

Abstract: Background Catheter ablation improves symptoms and quality of life in patients with atrial fibrillation (AF); however, despite its benefit, women are less likely than men to undergo catheter ablation. Women with AF have been described to have more frequent and severe symptoms with a lower quality of life than men, and it is therefore unclear why women are less likely to undergo catheter ablation. We prospectively characterized gender differences in AF symptoms among men and women undergoing ablation at UNC usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 36 publications
3
18
0
Order By: Relevance
“…However, most of these studies have used generic questionnaires and these are influenced not only by the arrhythmia but also by other causes, for example, concomitant diseases . In two recent studies, disease‐specific questionnaires were used confirming previously reported gender differences.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, most of these studies have used generic questionnaires and these are influenced not only by the arrhythmia but also by other causes, for example, concomitant diseases . In two recent studies, disease‐specific questionnaires were used confirming previously reported gender differences.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons suggested range from socioeconomic factors to fundamental gender differences regarding perception of illness . Bazemore et al made use of disease‐specific questionnaires but merely states that “this gender gap in enrolment for catheter ablation is unclear and likely due to multiple patient and provider factors.” Walters et al evaluated symptom severity and HRQoL also with disease‐specific instruments and found that psychological factors outweighed clinical predictors …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations